2019
DOI: 10.3389/fpls.2019.00653
|View full text |Cite
|
Sign up to set email alerts
|

The Plant DNA Damage Response: Signaling Pathways Leading to Growth Inhibition and Putative Role in Response to Stress Conditions

Abstract: Maintenance of genome integrity is a key issue for all living organisms. Cells are constantly exposed to DNA damage due to replication or transcription, cellular metabolic activities leading to the production of Reactive Oxygen Species (ROS) or even exposure to DNA damaging agents such as UV light. However, genomes remain extremely stable, thanks to the permanent repair of DNA lesions. One key mechanism contributing to genome stability is the DNA Damage Response (DDR) that activates DNA repair pathways, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(140 citation statements)
references
References 121 publications
1
122
0
Order By: Relevance
“…The DNA damage checkpoint exploits the available cell cycle regulatory machinery, i.e., cyclin-dependent kinases, cyclins and their regulators. In plants, it seems to be at least two-pronged: 1) ATM (and ATR) through SOG1 transcription factor [11,12] induce two types of CDK inhibitors, Wee1 kinase [11] and SIAMESE RELATED CDK inhibitors [14], both of which will lead to CDK inhibition [13,15]. Furthermore, SOG1 controls proteasome-dependent degradation of the mitotic CDKB2;1 [16].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA damage checkpoint exploits the available cell cycle regulatory machinery, i.e., cyclin-dependent kinases, cyclins and their regulators. In plants, it seems to be at least two-pronged: 1) ATM (and ATR) through SOG1 transcription factor [11,12] induce two types of CDK inhibitors, Wee1 kinase [11] and SIAMESE RELATED CDK inhibitors [14], both of which will lead to CDK inhibition [13,15]. Furthermore, SOG1 controls proteasome-dependent degradation of the mitotic CDKB2;1 [16].…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of genome integrity requires efficient DNA damage sensing and repair mechanisms (Cools and De Veylder, 2009;Nisa et al, 2019). Cells are constantly subjected to DNA damage arising from multiple origins, such as replication errors, mutations induced by the production of reactive oxygen species, or exposure to UV light, among others.…”
mentioning
confidence: 99%
“…Having established that MAIN, MAIL1, and PP7L acted in the same complex to prevent primary root growth arrest, accumulation of dead cells in the RAM, and release of TE silencing, we next aimed at understanding the mechanisms causing the observed mutant phenotypes. It is well established that activation of PCD in root initials is an important response to DNA damage (Hu et al ., ) and that spontaneous cell death in the RAM is a characteristic feature of mutants with impaired genome stability (Nisa et al , ). If cell death in pp7l‐1 and pp7l‐3 mutants was due to impaired genome stability, we would expect that the expression of DDR‐related genes would be increased.…”
Section: Resultsmentioning
confidence: 99%
“…We thus suggest that loss of function of MAIN and of its interaction partners MAIL1 and MIPP leads to genome instability and constitutive DNA damage resulting in root growth arrest. Recently, it was shown that in parallel to SOG1 another pathway involving the E2F transcription factors and RETINOBLASTOMA RELATED 1 (RBR1) controls the transcriptional response to DNA damage and the induction of cell death (Horvath et al , ; Nisa et al , ). It will be interesting to test whether this pathway is involved in the induction of cell death in the mutants described here.…”
Section: Discussionmentioning
confidence: 99%